2004
DOI: 10.1016/j.trstmh.2004.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Geophagy among pregnant and lactating women in Bondo District, western Kenya

Abstract: Geophagy was studied among 827 pregnant women in western Kenya, during and after pregnancy. The women were recruited at a gestational age of 14-24 weeks and followed-up to 6 months post-partum. The median age (range) of the women was 23 years and median parity 2. At recruitment, 378 were eating earth, of which most (65%) reported earth-eating before pregnancy. The preferred type of earth eaten was soft stone, known locally as odowa (54.2%) and earth from termite mounds (42.8%). The prevalence remained high dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 20 publications
9
29
0
6
Order By: Relevance
“…As reported previously (Luoba et al 2004), 45.7% were geophagous. The age of the women or their area of residence (a rough proxy of socio-economic differences) had no impact on this prevalence; neither were basic socio-economic factors significantly linked to geophagy (Luoba et al 2004). The women indicated a clear preference for particular kinds of earth: 54.2% ate 'soft stone' while 42.8% ate earth from termite mounds, others ate earth from earthen walls of houses and from gullies.…”
Section: Resultssupporting
confidence: 84%
“…As reported previously (Luoba et al 2004), 45.7% were geophagous. The age of the women or their area of residence (a rough proxy of socio-economic differences) had no impact on this prevalence; neither were basic socio-economic factors significantly linked to geophagy (Luoba et al 2004). The women indicated a clear preference for particular kinds of earth: 54.2% ate 'soft stone' while 42.8% ate earth from termite mounds, others ate earth from earthen walls of houses and from gullies.…”
Section: Resultssupporting
confidence: 84%
“…A. lumbricoides and hookworm infections were both significantly associated with geophagy, but no association was established between geophagy and T. trichiura or S. stercoralis. In consonant with results of previous studies 13,23 our present data, found that geophagy was associated with A. lumbricoides, T. trichiura and hookworm infections among pregnant women. Association of A. lumbricoides with geophagy was also recorded among school children in Kenya, Guinea and South Africa 6,9,26 .…”
Section: Discussionsupporting
confidence: 93%
“…The geophagous prevalence recorded is similar to others reported elsewhere in sub-Saharan Africa 10,11,13 . The results further revealed that although geophagy has been widely regarded as an obligatory response to a physiologic demand during pregnancy 9 , the behaviour is accepted culturally and perceived as a symbol of reproduction and fertility in the study area.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations